Foley Catheter versus Vaginal Misoprostol for Labour Induction - Nasreen Noor; Mehkat Ansari; S. Manazir Ali; Shazia Parveen (Hindawi Limited, 2015)
Objectives. To compare the efficacy and safety of intravaginal misoprostol with transcervical Foley catheter for labour induction. Material and Methods. One hundred and four women with term gestation, with Bishop score < 4, and with various indications for labour induction were randomly divided into two groups. In Group I, 25 μg of misoprostol tablet was placed intravaginally, 4 hourly up to maximum 6 doses. In Group II, Foley catheter 16F was placed through the internal os of the cervix under aseptic condition and then inflated with 50 cc of sterile saline. Statistical analysis was done using SPSS software. Results. The induction to delivery interval was 14.03 ± 7.61 hours versus 18.40 ± 8.02 hours (p<0.01). The rate of vaginal delivery was 76.7% versus 56.8% in misoprostol and transcervical Foley catheter group, respectively. Uterine hyperstimulation was more common with misoprostol. Neonatal outcome was similar in both the groups. Conclusion. Intravaginal misoprostol is associated with a shorter induction to delivery interval as compared to Foley's catheter and it increases the rate of vaginal delivery in cases of unripe cervix at term. Transcervical Foley catheter is associated with a lower incidence of uterine hyperstimulation during labour.